ANALISIS GERAK PENUMPANG PADA TABRAKAN FRONTAL DENGAN MENGGUNAKAN SIMULASI KOMPUTER - Ary Subagia, I.D.G; Kade Suriadi, I.G.A (Jurnal Energi Dan Manufaktur, 2012)
Frontal direction crash has become most serious cause in traffic accident. Based on the fact, this reaserch focused on the passenger movement in a frontal crash. The research was aimed to predict the direction of passenger movement and the benefit of using the seatbelt to decelerate the passenger movement in a frontal crash. The research was conducted by computer simulation by using Delphi 7. The inputs were vehicle velocity (80 km/h), mass of passenger (75 kg), and mass of vehicle (2000 kg). The results showed that in a frontal crash the deceleration of the passenger was smaller than that of the vehicle. The result of simulation showed that the force on passenger was 1.8352 N. If seatbelt tightness 1 N/cm2 was applied, the force on passenger decreased 468.56 N. In this case, the passenger still had relative velocity to the vehicle vrf = 1.75728 m/s and the force on passenger was 249.46 N. The seatbelt had important function to decelerate the passenger movement to the same deceleration of the vehicle during the frontal crash.
Keywords: Frontal crash, simulation, relative acceleration, passenger